An Empirical Analysis of Money Demand Function in Nepal - Budha, Birendra Bahadur (NRB Economic Review, 2011)
This paper analyzes the money demand function for Nepal during the period of the FY 1997/98 to FY 2009/10 using annual data. The empirical results imply that the cointegration tests clearly show the existence of the long-run relationship between real money balances and its determinants, output and interest rate. The vector error correction model has proved the short-run relationship between the real money balances and its determinants. Furthermore, Dynamic OLS estimation of the money demand function indicate that the sign of coefficients of the output and interest rate were found to be consistent with the assumption of the money demand theories.